(untitled) (REVUE DES SCIENCES DE LA SANTE, 2026)
Nosocomial infections (NIs) constitute a major cause of hospital morbidity and mortality, particularly in resource-limited countries. At the Hôpital Général de Référence de Nsona-Nkulu, their high prevalence is exacerbated by shortcomings in the continuing education of healthcare personnel. This study aimed to identify specific continuing education needs in order to improve the prevention and control of nosocomial infections. This was a quantitative, analytical, cross-sectional, and correlational study conducted from May to August 2025 among nurses working at the hospital. Data were collected using a self-administered questionnaire, supplemented by interviews and direct observations. Descriptive and correlational statistical analyses were performed, with the level of significance set at 5%. The findings revealed that the most frequent nosocomial infections were pneumonia (23.9%), bloodstream infections (19.7%), and surgical site infections (15.5%). The most affected departments were intensive care (34%), pediatrics (9.7%), and hemato-oncology (6.8%). The predominant pathogens identified were Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa, with multidrug resistance observed in 52.2% of the isolated strains. The main shortcomings identified included poor knowledge of hygiene protocols, insufficient continuous awareness activities, and inadequate equipment and resources. Logistic regression analysis identified two significant determinants of training needs: the lack of practical training and insufficient knowledge regarding nosocomial infections. The results also indicated that practical training significantly improves compliance with infection prevention protocols. In conclusion, combating nosocomial infections at the Nsona-Nkulu General Referral Hospital requires the implementation of an appropriate continuing education strategy based on regular educational programs, strengthened practical skills, and improved resources and working conditions.